(NgARMONIQ W MUZYKE (BXX (NWEKAs (NTEORIQs - (Nl(B.(Ns(B.(NdY^KOWAs ((NmOSKWAs (NpROBELs, 2003)
(Nw POSOBII DAETSQ HARAKTERISTIKA SOWREMENNOJ GARMONII(B, (NRASSMATRIWA@TSQ PROBLEMY ORGANIZACII WERTIKALI(B, (NLADOZWUKORQDNOGO MATERIALA(B.s
Keywords: (NtEORIQ(B.s